Teaching of Croatian as a second language to young learners : Minority language speakers and their Croatian competence - Jelaska, Zrinka (Array, 2009)
In this paper, after an insight into different minority languages within Croatia and their education possibilities and choices, different types of young Croatian L2 learners will be discussed. In past several years the acquisition of Croatian as L2 by children speakers of Roma, Hungarian and German language was investigated. The differences in proficiency of different groups of Croatian language learners will be shown. The differences will be interpreted according to the relevant factors that can influence it. Despite the fact that Croatian is a non-native language (L2) to some primary school children in Croatia, for years it has been taught as a first language (L1) to all of the students. Because of this and various other reasons (social, cultural, political, etc.) certain types of bilingualism are typical for the communities of particular first language (Italian, Hungarian, Roma, etc). Hence, within the borders of Croatia various groups of bilingual speakers can be differentiated: from balanced bilinguals to speakers of Croatian with very limited proficiency. Significant changes in Croatian language curriculum, teaching approaches and teacher training will be proposed in order to make teaching of Croatian to young minority language learners more in line with their needs.